Can a curriculum go through the process of aquilombamento? - Brito, Eliana Povoas Pereira Estrela (2020)
This article discusses the importance given to schools by quilombola communities. We argue that the school and its practices and modes of organization and functioning constitute a process of aquilombamento, which is understood as a way of resisting colonial impositions and ensuring the existence of the ancestral culture, traditions and inheritances of these communities. In the research, developed in a school at the quilombo Tomé Nunes (Bahia), we resorted to interviews and participatory observations for data collection and concluded that the struggle to create a curriculum that is connected to the process of aquilombamento in its political, geographic, historical and cultural aspects constitutes practices of resistance against the colonialist impositions established by current curricular policies.